Sistem Monitoring Realtime Jaringan Irigasi Desa (JIDES) Dengan Konsep Jaringan Sensor Nirkabel - Arie Setya Putra; Hamdan Sukri; Khozainuz Zuhri (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2018)
Self-sufficiency programs in the new government era program to regain food self-sufficiency that was once achieved. This is found in one of the new government initiatives, namely to realize national independence by mobilizing strategic sectors of the domestic economy, one of which is in the agricultural sector through efforts to build and realize food sovereignty. Based on this and in an effort to realize food sovereignty, the author made technological innovations in the form of prototype design of the village-based irrigation network monitoring system so that it can be accessed from various types of devices and can be accessed anywhere while the technology developed uses a single board computer (SBC) with sensor devices that have a detection distance of 2–300 cm and with a network model based on mesh topology which has a transmission distance of approximately 1200 meters outdoor between node points. Data transmission results between node points indicate that the water level data update time is every 60 seconds with the sending time to the server database on average every 60 seconds.